The effect of periodic thinning and stocking density on the growth and survival of sea bass Lates calcarifer (Bloch) - Dumada-ug, Cristeta R. (College of Fisheries, U. P. in the Visayas, 1990)
The effect of varying stocking densities and periodic thinning on the developemnt of shooters of juvenile seabass, Lates calcarifer (Bloch) at the nursery phase was studied. The shooting effect of seabass in the nursery phase was also investigated. The study which utilized a completelynrandomized design (CRD) tested four densities (3,4,6 and 9 fry per liter) which served as the different treatments. Each treatments was replictaed 6 times in 20 liter white plastic basins. Filtered seawater was used and salinity was maintained at 20 ppt. The fish were fed with Artemia salina, coperods (Entoomstracans), Mysids and trash fish for 35 days following a feeding schedule. thinning was made every seven days. Results indicated that periodic thinning of the seabass population every 7 days significantly reduced the developemnt of shooters by as much as 50% of 39 to 60 day old seabass. A stocking density of 9 juveniles per liter had the most number of shooters, while 6 juveniles per liter had the least number of shooters and a more or less even-sized population observed in this study falls between 4-6 seabass juveniles per liter of water. The initial size was 6.25 mm and the final size after 35 days was 24.18 mm. survival rates obtained in the study ranged from 89.60% to 35.0%